Demographic characteristics and prognostic indicators of childhood burn in a developing country (2014)
Children constitute a significant proportion of burn victims in most studies from the developing countries. While there has been a progressive improvement in the outcome from childhood burn in many developed nations, the morbidity and mortality remains high in many low and middle income countries. The aim of our study is to evaluate the demographic characteristics and prognostic indicators of childhood burn in a major referral teaching hospital in a developing country. A review of the records of 638 patients with acute burns managed over a 10-year period from January 2001 to December 2010 at the University College Hospital, Ibadan Nigeria was done. The clinical and epidemiological data were retrieved from computerized data base using the ISBI proforma. Information obtained includes Biodata, Etiology, location, TBSA, presence of Inhalation injury and the treatment outcome. Data of patients aged 16 years and below were analyzed using the SPSS version 16. The main outcome measure was the patient’s survival. 289 children representing 45.3% of the total number of burn patients were managed over the period. The M:F ratio was 1.1:1. The median age of the cohort was 4.0 years while the median TBSA was 21.0%. Nonintentional causes were responsible for 89.6% cases. Most of the injuries (88.6%) occurred at home. Eighty-three patients had inhalation injury out of which 57 (68.7%) deaths were recorded. The overall mortality rate in the cohort was 39.5% with an LA50 of burn size of 45%. The TBSA was also found to be a determinant of outcome. Majority of childhood burns are from preventable causes with attendant dismal mortality figures. Effective burn prevention strategies and improved quality of care remain pivotal in reducing childhood burn morbidity and mortality in the developing countries.